2015
DOI: 10.1093/jhered/esv025
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Genetic Diversity and Increased Dispersal in Guigna (Leopardus guigna) in Chilean Fragmented Landscapes

Abstract: Landscape fragmentation is often a major cause of species extinction as it can affect a wide variety of ecological processes. The impact of fragmentation varies among species depending on many factors, including their life-history traits and dispersal abilities. Felids are one of the groups most threatened by fragmented landscapes because of their large home ranges, territorial behavior, and low population densities. Here, we model the impacts of habitat fragmentation on patterns of genetic diversity in the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 134 publications
0
25
0
1
Order By: Relevance
“…Second, migration rates between northern and southern sites were also found to be directional, with higher levels of gene flow going from the north to the south (21% of individuals for this generation), than from southern to northern regions (9%) ( Fig 7 ; Table 6 ). Although ocelots are still considered widely abundant across Central America, they are understudied, and we found that the effects of habitat loss and fragmentation may have the potential to severely reduce genetic connectivity, which has been documented in ocelots at the northern extent of their range (e.g., [ 78 ]) and other small felid populations (e.g., [ 112 , 113 ]).…”
Section: Discussionmentioning
confidence: 86%
“…Second, migration rates between northern and southern sites were also found to be directional, with higher levels of gene flow going from the north to the south (21% of individuals for this generation), than from southern to northern regions (9%) ( Fig 7 ; Table 6 ). Although ocelots are still considered widely abundant across Central America, they are understudied, and we found that the effects of habitat loss and fragmentation may have the potential to severely reduce genetic connectivity, which has been documented in ocelots at the northern extent of their range (e.g., [ 78 ]) and other small felid populations (e.g., [ 112 , 113 ]).…”
Section: Discussionmentioning
confidence: 86%
“…Overall Hd and π were 0.982±0.012 and 0.02589, respectively. These results demonstrated Altai and Gobi populations have low genetic diversity with high genetic differentiation, hinting the subpopulations within these two populations have been isolated from each other and may lead to reduction in population size [20], [21].…”
Section: Mitochondrial Hvs Diversitymentioning
confidence: 82%
“…Other explanation could be that Guignas kill more animals than Darwin´s Foxes and can repeat predation events on poultry, thus providing people with a negative perception towards them. When inquired about damage caused by poultry depredation, most respondents in both study areas considered both Darwin's Foxes and Guignas to be damaging or very (Molina 1795), even though comparatively fewer real incidents occur nowadays. The high proportion of negative attitudes reported in some studies (Stowhas 2012;Herrmann et al 2013) seems unjustified or at least not proportionally linked to the amount of the currently caused damage, considering that the reported attacks performed by Guignas and Darwin's Foxes seem to be rare events and that the actual livestock and poultry losses are low.…”
Section: Discussionmentioning
confidence: 99%